Quantitation and Adsorption of Glyphosate Using Various Treated Clay - Mattos, Rodrigo; Khan, Sabir [UNESP]; Hussain, Sajjad; De Alencar Simoni, José (De Gruyter, 2017)
The objective of this work is to develop a low-cost, alternative UV-visible Spectrophotometer method using ninhydrin to the current chromatography techniques (GC and HPLC), which is usually use for the quantitation of glyphosate. The physico-chemical characterization, such as adsorption capacities, effect of time and temperature has been studied. The reaction between the ninhydrin and compounds that present NH2 group, which leading to the formation of a solution of blue coloration, has been analyzed by spectrophotometrically at 570 nm. The experimental data demonstrate equilibrium statistics, were well fitted to Langmuir isotherm. Adsorption kinetics of glyphosate on the adsorbent has been also analyzed by pseudo-first-order and pseudo-second-order models. The adsorption process is favored by acidic pH and followed the second-order kinetics. It was found that adsorption as a function of temperature, increase the temperature, decreases the adsorption. The isotherms shows the adsorption tendency like Arg-Na<Arg-Ca<Arg-Zn<Arg-Al, Arg-Cu with the variation of pH, it was found that at pH 6.5 has greater adsorption than pH 3.0. The important information which has been obtained from this work is to perform adsorption isotherms of glyphosate in clay soils with different metals such as Sodium, Calcium, Zinc, Copper (II) and Aluminum (Na+, Ca2+, Zn2+ ,Cu2+ and Al3+) in terms of models under different conditions of pH and temperature. It is noted that the rates of adsorption initially are fast and reached to maximum capacity up to 24 h in clay soil with sodium.
Keywords: adsorption isotherms; kinetics; pesticide; soil; UV-Vis spectroscopy